Morphogenetic constrains in the development of gastruloids: implications for mouse gastrulation - Ulla-Maj Fiuza; Bonavia, Sara; Pascual-Mas, Pau; Torregrosa-Cortes, Gabriel; Casani-Galdon, Pablo; Robertson, Gaelle; Dias, Andre; Alfonso Martinez Arias (bioRxiv, 2024)
Mammalian embryonic size is tightly controlled with checkpoints and compensatory mechanisms correcting size defects. Here, we take advantage of gastruloids, a stem cell embryoid system not subject to most size controls, to study the role of size in emergent properties of mammalian embryogenesis. We report that gastruloids exhibit robust morphology and transcriptional profiles within a size range. However, size affects the dynamics, and, outside a range of robust morphogenesis, the precision of anterior-posterior (AP) axial elongation. Gastruloid axial elongation exhibits active cellular contractility, requires planar cell polarity (PCP), adhesion and cell-cell contact remodelling. Smaller gastruloids initiate elongation earlier, correlated with an earlier Brachyury polarisation. Brachyury expression increases tissue fluidity. Axis formation is regulated by the balance of Brachyury multifoci coalescence and the timing of initiation of the elongation programme. Sizes beyond the robust range can modify relative tissue composition. Very small aggregates have increased neural fate bias, accompanied by a loss of paraxial mesoderm mediated by differences in Nodal signalling activity.Competing Interest StatementAMA is an inventor in two patents on Human Polarised Three-dimensional Cellular Aggregates PCT/GB2019/052670 and Polarised Three-dimensional Cellular Aggregates PCT/GB2019/052668.Footnotes* Competing interests statement and authors list.